Eating behavior and nutritional assessment in transgender people from an Outpatient Clinic for LGBT in Recife: Nutritional aspects of a transgender population in Recife - Gonçalves Machado, Juliana; Medeiros Araújo, Juciany; Caroline Silva dos Santos, Carla (Journal of Health Care, 2021)
Introduction: To be transsexual or transvestite is to be divergent from the gender norms established by society and to fight for the equality of your rights on a daily basis. After much struggle for equity, this population has access to the transsexual process in the Unified Health System today. However, little is discussed about the food and nutritional aspects present in the health of the trans. Objective: The purpose of this study was to know the sociodemographic profile, nutritional status and eating behavior of transsexual and transvestite people in an LGBT clinic in the city of Recife. Materials and Methods: This is a descriptive and quantitative approach of an exploratory, cross-sectional, analytical-descriptive study, which has a mixed approach. Results: From a sample of 15 participants, a young profile was identified, with medium/high schooling and employed formally or informally, with less social vulnerability when compared to other studies. Regarding the nutritional situation, overweight and cardiovascular risk prevailed, as well as in the Brazilian population. Finally, the body satisfaction found was regular and there were few people with an indication of eating behavior disorder. The scientific literature points out the risks of this population for image and eating disorders, in addition to the need for further studies on this topic, especially in view of the metabolic changes generated by the transexualizing process through hormone therapy, for example. Conclusion: The work highlights the importance of clinical follow-up with a comprehensive view, including the nutritional aspect for transgender people, and the strengthening of the health care network to ensure comprehensive care.
Keywords: Transgender person; Health Services for Transgender Persons; Nutrition for Vulnerable Groups; Nutritional Status; Feeding and Eating Disorders